Preparation of nanocrystalline CeO2 by the precipitation method and its improved methane oxidation activity - Choi, HJ; Moon, J; Shim, HB; Han, KS; Lee, EG; Jung, KD (WILEY, 2006)
Nanocrystalline CeO2 as small as 5 nm was successfully prepared by the precipitation method using hydrogen peroxide as an oxidizer. The methane oxidation temperature of this nanocrystalline CeO2 dropped about 100 degrees C as compared with microcrystalline CeO2.
Keywords: HYDROTHERMAL SYNTHESIS; CERIUM OXIDE